Tempo amigo ou inimigo? conceptualizações metafóricas de tempo no discurso feminino - Faraco, Solange Pereira Diniz (2008)
This research investigates the concept of time for the contemporary woman, using the Conceptual Metaphor Theory (LAKOFF e JOHNSON, 1980/2002, 1999; KÖVECSES, 2001, 2005; LAKOFF, 1987, 1993, 2004, GIBBS e STEEN, 1994, and others) as theoretical foundation. Based on this cognitive linguistic approach to metaphor, which suggests that our concepts are influenced by social and cultural dimensions, I investigate the conceptualization of time and its potential implications for Brazilian mature women, aged between 48-58 years old, living in urban and rural areas. The corpus used in this research consists of women s discourse and discourse aimed at women and comes from three different sources: media texts published in magazines whose readers are middle class adult women; the transcription of tape recorded talk of 6 women during organized social reading events in a medium sized town in the state of Rio de Janeiro; and the transcription of life histories produced by 5 women living in a remote rural area in the state of Minas Gerais, obtained during semi-structured interviews. The data used in the research were analyzed based on Cameron (2003, 2006), Charteris-Black (2004, 2005) e Musolff (2004). Some of the conceptual metaphors inferred are evidenced in the three types of discourse, however, the motivation for those metaphors are not the same ones.